2016
DOI: 10.1002/da.22559
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of suicidal behavior in high risk psychiatric patients using an assessment of acute suicidal state: The suicide crisis inventory

Abstract: The SCI was predictive of future SB in high-risk psychiatric inpatients during the crucial weeks following their hospital discharge. Further validation in diverse patient populations is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
154
0
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 116 publications
(166 citation statements)
references
References 55 publications
7
154
0
5
Order By: Relevance
“…A recent meta‐analysis also revealed that the experience of emotional pain was predictive of current suicidal ideation and attempts (Ducasse et al, ), suggesting its role in imminent suicide. Our studies with the STS found that emotional pain was a significant predictor of suicidal behavior within a month (Galynker et al, ). It must be noted that emotional pain may be strongly linked to entrapment (Bloch‐Elkouby et al, unpublished data), as suggested by the concept of “frantic hopelessness,” and future research may uncover emotional pain to be part of Criterion A.…”
Section: Suicide Crisis Syndromementioning
confidence: 79%
See 3 more Smart Citations
“…A recent meta‐analysis also revealed that the experience of emotional pain was predictive of current suicidal ideation and attempts (Ducasse et al, ), suggesting its role in imminent suicide. Our studies with the STS found that emotional pain was a significant predictor of suicidal behavior within a month (Galynker et al, ). It must be noted that emotional pain may be strongly linked to entrapment (Bloch‐Elkouby et al, unpublished data), as suggested by the concept of “frantic hopelessness,” and future research may uncover emotional pain to be part of Criterion A.…”
Section: Suicide Crisis Syndromementioning
confidence: 79%
“…In part to pay homage to these distinguished suicide researchers, the SCS name was derived from this term, as it was used to describe the intense affective state preceding an imminent suicide attempt. Further, because the development of the SCS stability and structure was confirmed by several factor analyses (Galynker et al, ; Yaseen et al, ; Yaseen et al, ; Yaseen et al, ), we felt justified in using the term syndrome in its widely accepted definition of several symptoms that occur together (American Psychiatric Association, ). A prodromal suicidal state was also considered, but its use can be problematic, as prodromes can last years (as in Bipolar Disorder), while the SCS is a true state phenomenon akin to state anxiety (Galynker, ).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…These proposed syndromes posit severe affective disturbance combined with physiological arousal and varying degrees of cognitive disturbance as syndromal states driving a transition to suicidal action. However, measures of anhedonia have not yet been incorporated into the measures aimed at assessing these syndromes (Galynker et al., ; Hawes, Yaseen, Briggs, & Galynker, ; Rogers et al., ; Stanley, Rufino, Rogers, Ellis, & Joiner, ; Tucker, Michaels, Rogers, Wingate, & Joiner, ; Yaseen et al., ; Yaseen et al., ; Yaseen, Gilmer, Modi, Cohen, & Galynker, ). Our findings suggest that measures targeting acute anhedonia, such as the SLIPS (Winer et al., ), could be an important addition to the assessment of these syndromes.…”
Section: Discussionmentioning
confidence: 99%